The trouble with 'Categories': Rethinking men who have sex with men, transgender and their equivalents in HIV prevention and health promotion. Issue 7 (13th September 2016) - Parker, Richard; Aggleton, Peter; Perez-Brumer, Amaya G.
ABSTRACT: This double Special Issue of Global Public Health presents a collection of articles that seek more adequately to represent sexual and gender diversities and to begin to rethink the relationship to HIV prevention and health promotion – in both the resource rich nations of the global North, as well as in the more resource constrained nations of the global South. Reckoning with the reality that today the global response to HIV has failed to respond to the needs of gay, bisexual and other men who have sex with men, and transgender persons, we turn our attention to processes and practices of categorisation and classification, and the entanglement of the multiple social worlds that constitute our understanding of each of these categories and people within the categories. Jointly, these articles provide critical perspectives on how defining and redefining categories may impact the conceptual frameworks and empirical evidence that inform global understandings of HIV infection, those communities most vulnerable, and our collective response to the evolving HIV epidemic.